Avoidant attachment attenuates the need-threat for social exclusion but induces the threat for over-inclusion - Izaki, Tsubasa; Wang, Wei; Kawamoto, Taishi (Frontiers in Psychology, 2022)
The influence of attachment style—anxious (AX) and avoidant (AV) attachment—on subjective responses to socially excluded experiences termed “Need-Threat” remains inconsistent. Need-Threat is a composite score of four fundamental needs: belonging, self-esteem, control, and meaningful existence. Individuals with high AX tend to spend much effort maintaining strong connections with others, while those with high AV tend to maintain high levels of self-esteem by distancing themselves from others. Therefore, attachment style is highly likely to influence the need associated with each style. In addition, since individuals with high AV satisfy their needs by keeping independence from others, they would experience the Need-Threat against excessive inclusion from others. The present study aimed to investigate the influence of attachment style on each Need-Threat response to various inclusionary statuses. A total of 133 undergraduate students were equally assigned to low or high groups for each attachment style. Participants played one of three types of the cyberball task (a ball tossing game with programed players): excluded, included, or over-included situation. The high AV group felt fewer threats to self-esteem than the low AV group in the excluded situation (p = .02). Furthermore, only in the over-included situation did the high AV group feel more threats to belonging and self-esteem than the low AV group (ps < .02). AX had no influence in any situation. These findings suggest that individuals with high AV would have a restrictive alleviation effect on adverse subjective responses to socially excluded experiences but demonstrate maladaptive subjective responses to over-included experiences.